Sistem Pengupahan Petani Kelapa Sawit Didusun Durian Takar Kecamatan Kemuning : Suatu Tinjauan Ekonomi Islam - Ria Ariska; Sissah Sissah; Ahsan Putra Hafiz (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This study aims to determine the wage system for oil palm farmers in Dusun Durian Takar, Kemuning District: an Islamic economic review, and how Islamic economic values ​​are applied in the wage system for oil palm farmers in Dusun Durian Takar Kemuning district. This study used a qualitative research type, the subjects of this study were the owners of the plantations and oil palm farmers, while the object was the wage system for oil palm farmers in Durian Takar village, Kemuning sub-district in an Islamic economic review. The sampling technique was obtained through data sources with consideration (certain criteria) based on a sample data source totaling 14 oil palm farmers, the data collection techniques in this study were interviews and documentation, and the analysis techniques used interactive analysis, namely, data reduction, data presentation , and drawing conclusions. The results of this study indicate that the wage system for oil palm farmers in the Durian Takar hamlet, Kemuning sub-district: an Islamic economic review, because the garden owners discuss in advance the amount of wages to be given so that the farmers can find out the wages given for each type of work in the management of oil palm plantations, and the garden owner discussed the procedure for payment, the garden owner did not delay payment of wages, wages were given directly to workers after the work was completed.